Evolution and Innovation of Social Insurance Policies for New Forms of Employment - Zhang, Haoxiang (International Journal of Social Sciences and Public Administration, 2024)
This paper aims to explore the evolution and innovation of social insurance policies for new forms of employment. Firstly, it defines the concept and features of new forms of employment, emphasizing their flexibility, temporariness, and digitization. Secondly, it analyzes the shortcomings of traditional social insurance policies in addressing the challenges posed by new forms of employment, including incomplete coverage and insufficient protection. Then, it summarizes the current research status and main viewpoints on this issue through a comprehensive review of domestic and international studies. Lastly, it discusses the evolution paths and innovative measures of social insurance policies for new forms of employment adopted by various countries.